Model Hubungan antara Dewan Pengawas Syariah dan Auditor Eksternal dalam Bank Syariah: Tinjauan Literatur dan Penerapan Prinsip-Prinsip Syariah pada Laporan Keuangan - Rizal, Muhammad; Qalbia, Farah; Seger Santoso (Al-Urban: Jurnal Ekonomi Syariah dan Filantropi Islam, 2023)
This study aims to examine the relationship between the Sharia Supervisory Board (SSB) and external auditors in Islamic banks, as well as the implementation of Sharia principles in financial statements. Through a qualitative literature review, it was found that the SSB plays a crucial role in ensuring that all bank activities comply with Islamic law, while external auditors are responsible for providing an opinion on the financial statements' compliance with Sharia principles. Despite the synergy between the two, significant challenges arise regarding competence, independence, and the standards used in implementing Sharia principles in financial reporting. This study also highlights the need for further training for both the SSB and external auditors, as well as standardization in the application of Sharia principles in Islamic banks' financial statements. A better collaboration between the SSB and external auditors can enhance transparency and accountability in Islamic bank operations